(untitled) (Research, Society and Development, 2022)
Objective: to update data on the three drugs recommended in the Brazilian Obesity Guideline (2016) – sibutramine, orlistat and liraglutide – gathering new evidence produced in the last 5 years. Methodology: A literature review was performed using the PubMed, Scopus and Embase databases, including studies published between 2017 and 2021, without language restriction. Results: In total, 21 studies were included, which brought new evidence on sibutramine, orlistat and liraglutide. Final considerations: Sibutramine proved to be safe and effective in obese patients with low cardiovascular risk, orlistat has relevant results in the treatment of polycystic ovary syndrome and non-alcoholic fatty liver, but it still has unpleasant adverse reactions and liraglutide shows up promising, causing consistent weight loss and few adverse effects. On the other hand, new clinical trials, systematic reviews and meta-analysis are needed to raise new evidence of efficacy and safety on the topic.